CCAFS annual report 2010: World’s largest coalition of researchers on climate change, agriculture and food security gears up - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
2010 saw the culmination of the most significant reform of the CGIAR system in its some 40 years of existence. A key element of this reform was the reorganization of the CGIAR around research programs that cut across Centres. One of the new research programs is on climate change. Because the Challenge Program was well positioned in terms of having initiated work on climate change, it was asked to lead the process of developing an expanded climate change program, one of only two fast-tracked programs. The climate change portfolio in the CGIAR is now expected to at least treble in size in 2011. The partnership in the new program represents the largest coalition of scientists working on the nexus between agriculture and climate change.